Analisis Penerapan 5 Bunga Pendidikan Karakter Pada Sekolah Dasar Di Purwakarta - Dwi Octaviani Putri; Cici Isnawati; Dede Wahyudin; Jennyta Caturiasari (FKIP, Universitas Palangka Raya, 2024)
This study aims to determine the policies of the Government of Purwakarta Regency regarding the implementation of character education policies. The research approach used is descriptive analysis. With the data collection method in the form of interviews with curriculum officers at one of the public elementary schools in Purwakarta district. From the results of observations, the techniques used were literature study and interviews. The instruments used were an analysis of the literature and interviews as a guide. The results of this study found that the organization of the implementation of character education policies in Purwakarta Regency was in accordance with Perbub no. 69 of 2015 was developed through several policies namely 5 (Five) Pillars of Character Education. The five flowers of character education include Seven Poe Atikan Purwakarta Istimewa, Religious Education and Book Deepening, Anti-Corruption Education Insertion, Child Friendly Schools, and Tatanen in Bale Atikan. With the enactment of the Perbup, character building must begin in the classroom and in each learning activity by adopting a useful and innovative learning model, namely the Pancaniti learning model which is rooted in Sundanese philosophy.